Process optimisation for ready to eat Indian mackerel (Rastrelliger kanagurta) curry in high impact polypropylene (HIPP) containers using still water spray retort - Dinakaran, Ammu; Mohan, C. O.; Panda, Satyen Kumar; Ravishankar, C. N.; Srinivasa Gopal, T. K. (Indian Journal of Fisheries, 2017)
Mackerel curry is a traditional food which is considered as a delicacy in Kerala. Indian mackerel curry was prepared as per standard recipe and hot filled into high impact polypropylene (HIPP) containers. Dynopack sealing machine was used for top sealing using see through films comprising polyester, silicone dioxide coated nylon and cast polypropylene and processed in a still water spray retort at 121.1°C to different F0 values of 6, 7 and 8 min. Based on the sensory and commercial sterility test, F0 value of 8 min was found to be optimum for mackerel in curry medium. The fish curry processed to F0 value of 8 was taken up for storage studies at ambient temperature (28±2°C) and changes in biochemical parameters like thiobarbituric acid (TBA), total volatile base nitrogen (TVBN), trimethylamine (TMA), instrumental colour and texture were analysed. Upon thermal processing, significant increase in chewiness as well as springiness and decrease in hardness was observed for mackerel at optimum F0 value. The product was found to be commercially sterile throughout the period of storage and was found to have a shelf life of 75 days.